Dysfunctional T cell metabolism in the tumor microenvironment. (June 2017) - Beckermann, Kathryn E.; Dudzinski, Stephanie O.; Rathmell, Jeffrey C.
Graphical abstract: Highlights: T cell fates are driven by cytokines and coordinate metabolic pathways. The tumor microenvironment is inhospitable for infiltrating lymphocytes by limiting nutrient resources and excretion of inhibitory signals. Current work is seeking to modify T cell signaling and metabolic pathways to work in synergy with current cancer immune checkpoint inhibitor therapy. Abstract: Metabolic and signaling pathways are integrated to determine T cell fate and function. As stimulated T cells gain distinct effector functions, specific metabolic programs and demands are also adopted. These changes are essential for T cell effector function, and alterations or dysregulation of metabolic pathways can modulate T cell function. One physiological setting that impacts T cell metabolism is the tumor microenvironment. The metabolism of cancer cells themselves can limit nutrients and accumulate waste products. In addition to the expression of inhibitory ligands that directly modify T cell physiology, T cell metabolism may be strongly inhibited in the tumor microenvironment. This suppression of T cell metabolism may inhibit effector T cell activity while promoting suppressive regulatory T cells, and act as a barrier to effective immunotherapies. A thorough understanding of the effect of the tumor microenvironment on the immune system will support the continued improvement of immune based therapies for cancer patients.